Neuroinflammatory Triangle Presenting Novel Pharmacological Targets for Ischemic Brain Injury - Shaheryar, Zaib A.; Khan, Mahtab A.; Adnan, Ch. Sherjeel; Zaidi, Awais Ali; Hänggi, Daniel; Muhammad, Sajjad (Frontiers in Immunology, 2021)
Ischemic stroke is one of the leading causes of morbidity and mortality globally. Hundreds of clinical trials have proven ineffective in bringing forth a definitive and effective treatment of ischemic stroke except a myopic class of thrombolytic drugs. That too, has little to do with circumscribing long-term post-stroke disabilities. These studies proposed diverse options to treat stroke ranging from neurotropic interpolation to venting antioxidant activity; from blocking specific receptors to obstructing functional capacity of ion channels; and more recent the utilization of neuroprotective substances. However, state of the art knowledge suggest that more pragmatic focus in finding effective therapeutic remedy of stroke might be targeting intricate intracellular signaling pathways of ‘neuroinflammatory triangle’; ROS burst, inflammatory cytokines and BBB disruption. Experimental evidence reviewed here support the notion that allowing neuroprotective mechanisms to advance acquiescently, while limiting the neuroinflammatory cascades, will help confine the post-stroke damage and disabilities.